LONG-TERM OUTCOME OF ART IN PATIENTS WITH HIV INFECTION IN THE EXAMPLE OF ANDIJAN REGION (Multidisciplinary Journal of Science and Technology, 2026)
Enhancing ART efficacy in HIV-infected children is a pressing objective for Uzbekistan's healthcare. This study evaluates the long-term impact of therapy in children under 14 in the Andijan region. Retrospective and prospective analyses demonstrated that strict adherence to treatment protocols significantly restores immune cells and mitigates opportunistic disease risks. The findings serve as a clinical platform for refining local protocols and territorial monitoring.